Semi-solid Sucrose Stearate-Based Emulsions as Dermal Drug Delivery Systems - Klang, Victoria; Schwarz, Julia C.; Matsko, Nadejda; Rezvani, Elham; El-Hagin, Nivine; Wirth, Michael; Valenta, Claudia (Pharmaceutics, 2011)
Mild non-ionic sucrose ester surfactants can be employed to produce lipid-based drug delivery systems for dermal application. Moreover, sucrose esters of intermediate lipophilicity such as sucrose stearate S-970 possess a peculiar rheological behavior which can be employed to create highly viscous semi-solid formulations without any further additives. Interestingly, it was possible to develop both viscous macroemulsions and fluid nanoemulsions with the same chemical composition merely by slight alteration of the production process. Optical light microscopy and cryo transmission electron microscopy (TEM) revealed that the sucrose ester led to the formation of an astonishing hydrophilic network at a concentration of only 5% w/w in the macroemulsion system. A small number of more finely structured aggregates composed of surplus surfactant were likewise detected in the nanoemulsions. These discoveries offer interesting possibilities to adapt the low viscosity of fluid O/W nanoemulsions for a more convenient application. Moreover, a simple and rapid production method for skin-friendly creamy O/W emulsions with excellent visual long-term stability is presented. It could be shown by franz-cell diffusion studies and in vitro tape stripping that the microviscosity within the semi-solid formulations was apparently not influenced by their increased macroviscosity: the release of three model drugs was not impaired by the complex network-like internal structure of the macroemulsions. These results indicate that the developed semi-solid emulsions with advantageous application properties are highly suitable for the unhindered delivery of lipophilic drugs despite their comparatively large particle size and high viscosity.